Development of Physics Comic 'History of Physics Series: The Development of Atom' - Maharani Ayu Nurdiana Putri; Anggi Aulidhia Rohmah; Aretha Patricia Andriani; Nadi Suprapto; Setyo Admoko (Universitas Lambung Mangkurat, 2021)
The quality of education can be improved by developing learning methods, curriculum development, and learning media development. One of them is learning media in the form of comics. This research aims to develop physics comics and analyze the validity of learning media of physics comics on the historical material of atomic development. The research was conducted using the R&D research model (Research and Development) with the 4-D model (Define-Design-Develop-Disseminate). Based on the stages, obtained learning media products that were declared eligible after validation by two high school physics teachers and an expert lecturer gained the average validity in the media component of 90.0%, the display of 89.2%, the material by 90.7%, and the language by 95.4%. In general, the student's responses to the use of physical comic learning media include comic physics can increase motivation in learning (88.6%), students prefer that physics learning uses comic media (88.9%), through comic media, students are introduced to atomic inventors (88.9%), and physics comics can help to understand the historical material of atomic development (83.3%). Based on the study results, learning media of physics comics on the historical material of atomic development deserves to be used in physics. The implication of this study can help other researchers as a reference related to the development of comic physics learning media.